Store-operated cyclic AMP signalling mediated by STIM1. - Lefkimmiatis, K; Srikanthan, M; Maiellaro, I; Moyer, M; Curci, S; Hofer, A (2009)
Depletion of Ca(2+) from the endoplasmic reticulum (ER) results in activation of plasma membrane Ca(2+) entry channels. This 'store-operated' process requires translocation of a transmembrane ER Ca(2+) sensor protein, stromal interaction molecule 1 (STIM1), to sites closely apposed to Ca(2+) channels at the cell surface. However, it is not known whether a reduction in Ca(2+) stores is coupled to other signalling pathways by this mechanism. We found that lowering the concentration of free Ca(2+) in the ER, independently of the cytosolic Ca(2+) concentration, also led to recruitment of adenylyl cyclases. This resulted in enhanced cAMP accumulation and PKA activation, measured using FRET-based cAMP indicators. Translocation of STIM1 was required for efficient coupling of ER Ca(2+) depletion to adenylyl cyclase activity. We propose the existence of a pathway (store-operated cAMP signalling or SOcAMPS) in which the content of internal Ca(2+) stores is directly connected to cAMP signalling through a process that involves STIM1.